Photodynamic Therapy, Probiotics, Acetic Acid, and Essential Oil in the Treatment of Chronic Wounds Infected with Pseudomonas aeruginosa - Jaeson D. Chin; Lei Zhao; Trenton G. Mayberry; Braydon C. Cowan; Mark R. Wakefield; Yujiang Fang (MDPI AG, 2023)
As a prevalent medical problem that burdens millions of patients across the world, chronic wounds pose a challenge to the healthcare system. These wounds, often existing as a comorbidity, are vulnerable to infections. Consequently, infections hinder the healing process and complicate clinical management and treatment. While antibiotic drugs remain a popular treatment for infected chronic wounds, the recent rise of antibiotic-resistant strains has hastened the need for alternative treatments. Future impacts of chronic wounds are likely to increase with aging populations and growing obesity rates. With the need for more effective novel treatments, promising research into various wound therapies has seen an increased demand. This review summarizes photodynamic therapy, probiotics, acetic acid, and essential oil studies as developing antibiotic-free treatments for chronic wounds infected with Pseudomonas aeruginosa. Clinicians may find this review informative by gaining a better understanding of the state of current research into various antibiotic-free treatments. Furthermore. this review provides clinical significance, as clinicians may seek to implement photodynamic therapy, probiotics, acetic acid, or essential oils into their own practice.